Pengaruh Kejelasan Sasaran Anggaran dan Pengendalian Internal terhadap Akuntabilitas Pengelolaan Dana Desa - Leoni, Prima Widitia; Andriani, Wiwik; Yentifa, Armel; Zahara, Zahara (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This study aims to determine and analyze the effect of clarity of budget targets and internal control on the accountability of village fund management. The data used in this study is primary data collected through a research instrument in the form of a questionnaire. The sample in this study was village officials in Hamparan Rawang District, totalling 115 people. The sampling technique in this study was purposive sampling, which was then analyzed using multiple linear regression analysis with the SPSS version 25 application and with a significance level of 5%. The results of this study indicate that the clarity of budget targets and internal control affect the accountability of village fund management.